Utilizing fillers for addressing speaking challenges, improving self-confidence and motivation in EFL learning - Syamsudin, Syamsudin; Istiadah, Istiadah; Syafiyah, Syafiyah; Cahyono, Agus Eko; Mulyono, Sugeng (Journal of Education and Learning (EduLearn), 2024)
This qualitative case study aimed to explore fillers usage to address speaking challenges related to the improvement of self-confidence and motivation in speaking practices done by two English foreign language (EFL) learners of the English department of one of the Islamic Universities in Malang, Indonesia. Data were collected through observations and in-depth interviews to two students employing filler strategies to address speaking challenges related to the improvement of self-confidence and motivation during their speaking exercises. The research revealed that both learners used fillers to address speaking challenges during the conversation due to their linguistic components’ shortage such as a limited mastery of vocabularies and having a little understanding on grammar. Fillers might bring them to have more self-confidence in speaking practices shown by not being afraid of making mistakes when they practice speaking with their speaking partners. Fillers might bring them to have more motivation in speaking shown by their enthusiasm to get involved in the discussion whether in group or class discussions. Thus, fillers usage is prominent due to its potential to address speaking challenges, enhance self-confidence and motivation, eventually contributing to an overall improvement in language proficiency particularly in speaking skill.